2017
DOI: 10.1049/iet-opt.2016.0069
|View full text |Cite
|
Sign up to set email alerts
|

Open circuit voltage recovery in quantum dot solar cells: a numerical study on the impact of wetting layer and doping

Abstract: We present a numerical study on the influence of wetting layer states and doping on the photovoltage loss of InAs/GaAs quantum dot solar cells. Quantum-mechanical simulations are used to analyze how the reduction of wetting layer by Al(Ga)As overgrowth changes the quantum dot electronic states. Device-level simulations allows to correlate such changes with the achievable open circuit voltage. Almost full open circuit voltage recovery is predicted by combining wetting layer reduction, to realize thermal decoupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Several issues need to be overcome in QDSCs, such as to avoid an important reduction of the open-circuit voltage (V OC ) that leads to a drop in the efficiency in comparison to their single junction GaAs SC counterparts [3,12]. It is said that the key prerequisite for improvement of the output voltage is the suppression of photoelectron capture from the conduction band into QD states which mainly occurs through the extended wetting layer (WL) state [13,14]. Certainly, it is demonstrated that the large phase volume of WL plays a major role in this V OC reduction [15], so QD properties can be radically altered if WL states are non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…Several issues need to be overcome in QDSCs, such as to avoid an important reduction of the open-circuit voltage (V OC ) that leads to a drop in the efficiency in comparison to their single junction GaAs SC counterparts [3,12]. It is said that the key prerequisite for improvement of the output voltage is the suppression of photoelectron capture from the conduction band into QD states which mainly occurs through the extended wetting layer (WL) state [13,14]. Certainly, it is demonstrated that the large phase volume of WL plays a major role in this V OC reduction [15], so QD properties can be radically altered if WL states are non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…The electron and hole confinement energy in the QD levels (e.g., for the GS level, ∆E e GS and ∆E h GS in Fig. 2) is estimated by assuming that 80% of the difference between the GaAs band gap (E g,B = 1.424 eV) and the QD level energy gap is allocated to the conduction band [40,39]. Since the thermally-dominated escape rate depends on the confinement energy, this implies that holes have a markedly faster dynamics than electrons.…”
Section: Electrical Modelmentioning
confidence: 99%
“…Thus, escape time constants are derived from capture and relaxation scattering times based on the argument of detailed balance at thermal equilibrium [21]. This modeling approach allows to single out the impact on the cell photovoltaic behavior of different and interplaying physical mechanisms, such as QD kinetics [23,38,39], non radiative recombination [21], and photon losses (by proper coupling with a suitable optical model) and thus it is very well suited for the interpretation of experimental results and the investigation of novel design solutions.…”
Section: Electrical Modelmentioning
confidence: 99%
“…[25]), making the QD carrier lifetime largely dominated by the QD radiative lifetime. Moreover, the open-circuit voltage (V oc ) penalty in thermally limited QDSCs is dominated by the ratio between carrier lifetime in the barrier and carrier lifetime in QDs [27], the last one being the net result of the competing processes of capture/relaxation/recombination through the QDs-from the one hand-and escape from the QD bound states and electric-field-driven sweep out through the extended states-from the other hand. Thus, at least in In(Ga)As/GaAs QDs and under nonconcentration operation, capture/relaxation times can be reasonably treated as constant parameters, neglecting their carrier density dependence and the possible electric-field dependence due to tunneling mechanisms.…”
Section: Modelmentioning
confidence: 99%